Ethno-Cultural Factors Influencing the Development of Rural Tourism in Kazakhstan - TLEUBAYEVA, Aitolkyn (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019, 2019)
This paper discusses the traditions and customs of the Kazakh people, such as some forgotten national crafts, dishes, sports and games, holidays as an integral part, i.e. ethno-cultural factors contributing to the development of rural tourism. In addition, the classification of the close relationship, Association and combination of rural tourism with other types of tourism was noted, as well as the tourist cluster approach in rural tourism was compiled and proposed by the author. In addition, the advantages that will be obtained as a result of the development of rural tourism, the problems that need to be addressed by the state in the field of tourism were demonstrated, the options for directions for the establishment and development of rural tourism and appropriate actions for its creation and formation were recommended.